2013
DOI: 10.1159/000350802
|View full text |Cite
|
Sign up to set email alerts
|

Cost and Effectiveness of Therapy for Wet Age-Related Macular Degeneration in Routine Clinical Practice

Abstract: Purpose: Evaluation of the cost and effectiveness of therapy for patients with the wet form of age-related macular degeneration (AMD) in routine clinical practice. Methods: A retrospective multicentre evaluation of changes in the best-corrected visual acuity in applied kinds of therapy and a comparison with the cost of individual therapeutic procedures. Results: An overall total of 788 eyes of 763 patients with an average age of 73.2 ± 8.6 years was evaluated for a 1-year minimum period. In the ranibizumab and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…Therefore, these studies might not be able to provide relevant information for decision-makers (Payet et al 2008). Studies conducted under clinical practice conditions, such as Phase IV, pragmatic clinical trials and observational studies, which are aimed to assess the effectiveness of treatments, could be of great value in order to confirm the efficacy results obtained in RCTs (Alban et al 1997;AMCP 2016;Bastida et al 2010;CADTH 2017;Capri et al 2001;CES 2004;Fukuda 2016;Heintz et al 2016;Infarmed 1998; L€ a€ akkeiden Hintalautakunta 2017; Payet et al 2008;PHARMAC 2015;SMC, 2017;Studni cka et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these studies might not be able to provide relevant information for decision-makers (Payet et al 2008). Studies conducted under clinical practice conditions, such as Phase IV, pragmatic clinical trials and observational studies, which are aimed to assess the effectiveness of treatments, could be of great value in order to confirm the efficacy results obtained in RCTs (Alban et al 1997;AMCP 2016;Bastida et al 2010;CADTH 2017;Capri et al 2001;CES 2004;Fukuda 2016;Heintz et al 2016;Infarmed 1998; L€ a€ akkeiden Hintalautakunta 2017; Payet et al 2008;PHARMAC 2015;SMC, 2017;Studni cka et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Closer to clinics, a comparative cost-effectiveness of therapy for age-related macular degeneration has been performed between Verteporfin (a ribonucleic acid aptamer targeting the vascular endothelium growth factor (VEGF) from Novartis Pharma AG) and Ranibizumab (a monoclonal antibody targeting a wider diversity of VEGF isoforms from Genentech Inc). It was found that the treatment cost with the aptamer was half that of the monoclonal antibody [104]. The difference is not as striking as could be expected, but an emerging consensus suggests that the costs should be slightly lower.…”
Section: Comparative Advantages In Using Aptamers Over Antibodiesmentioning
confidence: 95%
“…Z jejich analýz je také patrné, jaký význam má dostatečná frekvence kontrol a zejména aplikací. Pokud jsou pacienti léčeni dostatečně intenzivně, lze se i v reálné klinické praxi přiblížit vynikajícím výsledkům léčby v klinických studiích [16,17,28].…”
Section: Diskuseunclassified